The influence of birth weight amongst 33–35 weeks gestational age (wGA) infants on the risk of respiratory syncytial virus (RSV) hospitalisation: a pooled analysis. (17th January 2017) - Carbonell-Estrany, Xavier; Fullarton, John R.; Gooch, Katherine L.; Gouyon, Jean-Bernard; Lanari, Marcello; Rodgers-Gray, Barry S.; Thwaites, Richard J.; Vo, Pamela G.; Liese, Johannes G.
Abstract: Objective : To investigate the association between birth weight and respiratory syncytial virus (RSV) hospitalisation during the first year of life in 33°–35 6 weeks' gestational age (wGA) infants. Study design : Pooled analysis of data ( n = 1218) from Spain, Germany, France and Italy. Result : RSV hospitalised infants overall had a significantly higher birth weight than non-hospitalised infants (2.24 versus 2.14 kg; p < 0.001) for both males (2.25 versus 2.18 kg; p = 0.049) and females (2.22 versus 2.11 kg, p = 0.007). The effect was significant only in 34 wGA infants (33 wGA: hospitalised 1.95 kg versus non-hospitalised 1.95 kg, p = 0.976; 34 wGA: 2.26 versus 2.14 kg, p = 0.007; 35 wGA: 2.37 versus 2.29 kg, p = 0.070), particularly female 34 wGA infants (female: 2.24 versus 2.08 kg, p = 0.019; male: 2.27 versus 2.20, p = 0.191). Birth weight was shown to be an independent risk factor for RSV hospitalisation. Conclusions : In 33–35 wGA infants, a higher birth weight appeared independently associated with an increased risk of RSV hospitalisation.